Let's get active: Learning about Animals - Chowdhary, Eman (New Delhi The Energy and Resource Institute, 2016)
Most of us lead careless lifestyles that keep adding to environmental pollution. Carbon Footprint: Learning about Animals educates young learners about the wonderful world of animals. It explains interesting facts about the members of the animal kingdom, such as their food, homes, classifi cation, special features, and so on through spot-the-difference, maze, dot-to-dot, and colouring activities, besides simple counting and writing exercises. These easy-to-do activities promote creative thinking and problem solving among young minds, making the title a fun supplement to their textbooks, while acquainting them with these amazing beings.
Keywords: Animals; Activity book